Effect of diabetes on short-term mortality and incidence of first hospitalizations for cardiovascular events after recovery from SARS-CoV-2 infection. (May 2022) - Profili, Francesco; Seghieri, Giuseppe; Francesconi, Paolo
Abstract: Aim: To evaluate the impact of diabetes and COVID-19 on all-cause-mortality and first hospitalizations for cardiovascular events (CVE): myocardial infarction or stroke, within six months after being tested positive and having recovered from SARS-CoV-2 infection. Methods: Resident population in Tuscany, Italy of age 45–94 yr without prior hospitalization for CVE, tested positive for SARS-CoV-2 by March 1st, 2020 and afterwards recovering from COVID-19 was compared with age, gender and diabetes matched controls without infection, for incidence rate ratio (IRR) of all-cause-deaths or first CVE at six months follow up. Results: 46, 152 subjects of whom 4, 597 with diabetes, tested positive and recovered from SARS-CoV-2 were compared with 1:1 age, gender and diabetes matched controls without infection. COVID-19 was associated with higher all-cause-mortality: IRR:1.92(95 %CI:1.63–2.25) while diabetes with increased risk of first CVE hospitalizations: IRR:2.24(2.18–4.25). Co-presence of COVID-19 and diabetes didn't add any additional excess risk. Being women and statins' use significantly reduced death risk. Conclusions: After recovery from COVID-19, independently of diabetes, all-cause-mortality risk at six months was twofold increased, while risk of first CVE hospitalization remained unmodified. Diabetes, independently of prior COVID-19, resulted in higher six-months risk of first CVE not of death. Female gender and statins' use reduced both excess risks.